The extent of the industrial company's response to blue market strategy indicators: Applied research (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The current research aims to describe the level of responsiveness and awareness of the officials of the General Company for Construction Industries to the indicators of the blue market strategy of (1. reduction 2. exclusion 3. increase 4. innovation) and the degree of prioritization according to their importance as well as the differences in the responses of the sample investigated according to the personal variables. As a main tool in the collection of data from the sample, which consisted of(34) officers (Associate, Manager, Section Manager, Division Officer) in the company being investigated, and computed mean, standard deviations, percentage weights,and test (x2 )  based on the SPSS. The research reached the following conclusions: The level of response of the surveyed sample to blue market strategy indicators was positive and to a large extent, the ranking of these indicators according to their degree of importance was (increase, decrease, innovation, exclusion), There are statistically significant differences in the responses of the surveyed sample according to the personal variables (academic attainment, job position, years of service).